A More Sustainable Process for Preparation of the Muscarinic Acetylcholine Antagonist Umeclidinium Bromide. (31st August 2018) - Espadinha, Margarida; Lourenço, Nuno M. T.; Sobral, Luis; Antunes, Rafael; Santos, Maria M. M.
Abstract: A more sustainable process for the synthesis of the long‐acting muscarinic acetylcholine antagonist umeclidinium bromide is described. Specifically, we report the synthesis of ethyl 1‐(2‐chloroethyl)‐4‐piperidinecarboxylate, a key intermediate in the preparation of umeclidinium bromide, in good yields using triethylamine, as well as the identification and characterization of the by‐product formed in this reaction. This new method of synthesis leads to an improvement in yield over that of previously reported protocols using potassium carbonate as base (65.6 % versus 38.6 %). Moreover, in the final synthetic step of the process to obtain umeclidinium bromide, we were able to replace the use of toxic solvents (acetonitrile/chloroform) with water. The use of this green solvent allowed precipitation of the active pharmaceutical ingredient (API) from the reaction medium with high purity and in high yield. Overall, we have developed a more efficient and environmentally friendly process for the synthesis of the umeclidinium bromide API with a higher overall yield (37.8 % versus previously reported overall yield of 9.7 %). Abstract : It′s easy being green : Herein we report a more efficient and environmentally friendly process for the synthesis of the active pharmaceutical ingredient, umeclidinium bromide. This new synthesis protocol gives an improved yield over that of previously reported protocols using potassium carbonate as base. Moreover, in the final synthetic step of the process to obtain umeclidinium bromide, we were able to replace the use of toxic solvents (acetonitrile/chloroform) with water.